Intussusception in an infant complicating dengue infection - ., Fadila; Omair, Md. Faraz; Kevlani, Neeta (International Journal of Contemporary Pediatrics, 2020)
Intussusception is the most common abdominal emergency in children younger than 2 years of age. A 6-month-old child presented as dengue with gross abdominal distension to our hospital. Dengue was managed using standard therapy as per world health organization protocol, while abdominal pathology, later found out to be intussusception, required exploratory laprotomy. At the outset, abdominal distensions in the setting of a severe dengue infection, could be misdiagnosed as ascites due to capillary leakage, masking the clinical findings of acute abdomen on examination. Although unusual, it is possible to find two concurrent illnesses simultaneously, one complicating the typical clinical course expected from the other, and this needs high index of suspicion due to different management strategies of both. We describe here the diagnostic dilemma of such a case.